Contribution of the Portuguese Laboratory Network for the Diagnosis of Influenza A(H1N1)pdm09 Infection during the 2009/2010 and 2010/2011 influenza seasons - Portuguese Laboratory Network for the Diagnosis of Influenza Infection (2012)
This article describes the data obtained by the Portuguese Laboratory Network, reactivated following the World Health Organization declaration of the 2009 influenza pandemic, on the diagnoses of influenza A(H1N1)pdm09 infection during the pandemic (2009/10) and post-pandemic (2010/11) influenza seasons. The laboratories analysed and reported cases of influenza-like illness (ILI) and severe acute respiratory infection (SARI) to the National Influenza Reference Laboratory, which performed more detailed antigenic and genetic characterisation of the virus isolates. In 2009/10, a total of 62,089 ILI cases, distributed in two peaks, were analysed, 25,985 of which were positive for influenza A(H1N1)pdm09. Children aged 5–14 years were the most affected. Viruses were both antigenically and genetically similar to the pandemic strain A/California/7/2009, included in the 2009/10 pandemic vaccine. During the post-pandemic season, 1,496 ILI cases were tested for influenza A(H1N1)pdm09, 572 of which were positive. Infection was mainly diagnosed in adolescent and adults. Although the 2010/11 viruses remained antigenically similar to A/California/7/2009, increased genetic variation was observed. During the two seasons, two viruses with the neuraminidase H275Y amino acid substitution, associated with oseltamivir resistance, were detected. The Laboratory Network made an important contribution to the description of the influenza activity in the two seasons.